Techno-economic assessment of a biomass torrefaction plant for pelletized agro-residues with flue gas as a main heat source - Thossaporn Onsree (2021)
© 2020 The Authors Torrefaction combined with densification for upgrading biomass to torrefied biomass pellets is increasingly of great interest since torrefied biomass pellets are considered as a major renewable energy source. Especially in the application of co-firing with coal, torrefaction may be easily integrated into an existing co-firing power plant, whose flue gases from the power plant could be used to torrefy biomass pellets. This could also help to improve the overall carbon efficiency of the power plant and reduce emissions of greenhouse gases. In the present work, a torrefaction plant for corn residue pellets to produce torrefied solid fuels using flue gases as a main heat source was simulated in Aspen Plus® software. Torrefaction module was successfully modelled by an RYield reactor, which was programmed with the two-steps-in-series kinetic for the decomposition of biomass pellets as well as the volatile formation for by-products. The model can, therefore, provide the distribution and yield of both torrefied biomass pellets and volatile by-products. From the validation, the simulation results appeared to show good agreement with available experimental data in the literature. At the suggested conditions of 260 °C wet flue gas and 20 min residence time, thermal energy of 460 J/g and 380 J/g were required for the drying and the torrefaction modules, respectively. At these conditions, the performance of the whole process was found to be almost 95%. This plant produced 75% w/w torrefied biomass pellets yield with HHV of 21.9 MJ/kg. The by-products mainly included 10.7% w/w water, 7.4% w/w CO2, and 1.7% w/w CO. Our findings provide a feasible outlook for integrating a torrefaction process of biomass pellets into a co-firing power plant, utilizing a realistic heat of waste flue gases for the process.